2011
DOI: 10.3109/10903127.2010.541980
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Prehospital Morphine, Fentanyl, and Methoxyflurane in Pediatric Patients

Abstract: Intranasal fentanyl and intravenous morphine are equally effective analgesic agents in pediatric patients with moderate to severe acute pain in the out-of-hospital setting. Methoxyflurane is less effective in comparison with both morphine and fentanyl, but is an effective analgesic in the majority of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 38 publications
1
83
4
2
Order By: Relevance
“…Methoxyflurane was inferior in providing effective analgesia. Effective analgesia was defined as a reduction in pain score of 30% or greater [13]. However, another study found that methoxyflurane had a significant effect on pain reduction as assessed by provider and parents [14].…”
Section: Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Methoxyflurane was inferior in providing effective analgesia. Effective analgesia was defined as a reduction in pain score of 30% or greater [13]. However, another study found that methoxyflurane had a significant effect on pain reduction as assessed by provider and parents [14].…”
Section: Efficacymentioning
confidence: 99%
“…Two LOE-2 studies examined efficacy of analgesia. Opioids were included in both studies (Table 2) [13,15].…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Intranasal fentanyl has been shown to be effective in treating pediatric pain in the emergency department and prehospital settings. 24,25 Because this is a newer analgesic and route of analgesic administration in the prehospital setting, it is possible that with time and further training, paramedics will become more comfortable with its use in pediatric pain management. However, in the system studied, the paramedic option of intranasal fentanyl had been available for more than 2 years before this study was completed, suggesting that other factors discouraging its use may be at work.…”
Section: Table 4 Enablers For Pediatric Analgesic Administrationmentioning
confidence: 99%
“…(13) Studies conducted in prehospital settings have shown that intranasal fentanyl is as effective an analgesic as intravenous morphine in adult (14) and paediatric patients. (15) Although the evidence regarding the use of intranasal fentanyl in EDs is limited, the few published studies show promising results. In one study, intranasal fentanyl was shown to be as effective an analgesic as intramuscular morphine in children presenting to the ED.…”
Section: Introductionmentioning
confidence: 99%